Pengaruh Digital Transformation dan Digital Human Resources Management Terhadap Strategic Leadership yang Dimediasi oleh Organizational Culture pada Karyawan Perusahaan Retail di Jakarta Barat - Nabilah, Eva; Putra, Andreas Wahyu Gunawan; Togatorop, Stiven Klaudia (CV. Ulil Albab Corp, 2025)
This research aims to analyze the influence of Digital Transformation and Digital Human Resource Management on Leadership Strategy with Organizational Culture as a mediating variable. Digital transformation and digital human resource management are important factors in changing company strategy and culture. The research method used is quantitative with a survey approach. Data was obtained from a questionnaire distributed to employees of companies that have implemented digital technology in West Jakarta. The research results show that Digital Transformation has a positive effect on Organizational Culture, which in turn affects Leadership Strategy. Likewise, Digital Human Resource Management can increase the effectiveness of organizational culture, although its direct influence on Leadership Strategy is still limited. In conclusion, developing a strong organizational culture through digital transformation and digital human resource management plays an important role in strengthening leadership strategies in the digital era.